2018
DOI: 10.1016/j.jinf.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with the development of active tuberculosis among patients with advanced chronic kidney disease

Abstract: TB incidence was very high among those receiving renal replacement therapy or CKD 4 or 5. Most cases occurred in those of an Asian/Asian British or black/black British background. Testing and treating such patients for latent TB is justified and should include those who have been receiving renal replacement therapy for some years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…There are only few studies assessing the rates of active TB after SOT or dialysis in countries with low TB incidence, but our results are similar to findings from a Canadian study of SOT recipients [10], a study from the UK of patients with advanced chronic kidney disease [11], and an Australian study of dialysis patients [12]. It has previously been reported that rates of TB are 20-74 times higher in SOT recipients and patients on dialysis compared to the general population [13][14][15].…”
Section: Discussionsupporting
confidence: 86%
“…There are only few studies assessing the rates of active TB after SOT or dialysis in countries with low TB incidence, but our results are similar to findings from a Canadian study of SOT recipients [10], a study from the UK of patients with advanced chronic kidney disease [11], and an Australian study of dialysis patients [12]. It has previously been reported that rates of TB are 20-74 times higher in SOT recipients and patients on dialysis compared to the general population [13][14][15].…”
Section: Discussionsupporting
confidence: 86%
“…Patients with previously diagnosed DM often had serious comorbidities and DM complications such as chronic kidney disease which itself is an independent risk factor for TB [35], and microvascular and/or macrovascular complications. Patients with newly diagnosed DM had fewer DM complications, but more severe TB, despite better glycaemic control, suggesting that some of those newly diagnosed were experiencing "transient hyperglycaemia" due to severe TB.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Moreover, a previous study showed that patients with chronic kidney disease who developed pulmonary TB were significantly more likely to have received intravenous iron therapy, and iron is a co-factor supporting mycobacterial growth. 22 In our study, more than half of the patients had received intravenous iron treatment within the past year, which may also be a risk factor for the development of bone and spine TB.…”
Section: Discussionmentioning
confidence: 78%